A Singular Voltage Stability Indices Approach to Spot Out Weedy Bus Under Contingency Environment - Jayachitra Selvaraj (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Voltage stability estimation is one of the foremost parameter in monitoring the power system stability. Various voltage stability indices had been developed by researcher for voltage stability assessment. These indices were executed for spotting the pathetic transmission lines/buses. Here forth the placement and sizing of FACTS devices to trigger countermeasures against voltage instability/blackouts. In this paper two voltage stability indices were proposed called Synthesis Severity Index (SSI) and Compound Index (CI).These indices had been implemented on IEEE 14 and 30 bus system under generator and line contingencies. The resulted were presented and discussed.